The Definite Referring Expressions of the Prophet Muhammad's Implicated Speech and its Educational Value - Suhartono, Suhartono (International Journal for Educational and Vocational Studies, 2020)
The aims of this study is to analyze the definite referring expressions of the Prophet Muhammad's Implicated Speech and its Educational Value. This is qualitative study with the data in the form of dialogical utterances speech involving two parties, namely the Prophet Muhammad and his best friend. While the source of this research data is a collection of valid hadith narrated by Bukhari and Muslim. In this study, the data collected was analyzed with an explanatory comparative technique with Miles and Huberman's flow analysis techniques, namely data reduction, data presentation, and inference / verification. The results of this study indicate that the expression of certain reference in the implied implications of the Prophet Muhammad can be identified based on certain sciences, such as mathematics and linguistics. The use of this knowledge base is adjusted to the number and type of certain reference expressions used. By using a certain knowledge base, all definite reference expressions in the explicator can be identified so that the meaning is clear. Clarity of meaning that is associated with the context of communication or shared knowledge in this case is an important property of understanding implicates. For further explained, the expression of reference must be in the process of refinement, the process of refinement is in the explanatory, the exploitation is in the implied speech, the implied speech is in the pragmatic or speaking practice. This shows that the expression of reference must be at the point in speaking activities. The use of definite reference expressions, thus implies high-level speaking skills. Higher-level speaking skills are even better when identifying certain expressions of reference in the speech used requires mastering knowledge in mathematics, linguistics, and so on. In other words, the better the quality of a speech if the speaker is conditioned to operate the multidisciplinary knowledge he has in identifying the expression of certain reference because it has educational value.